THE MANAGEMENT OF THE M’ZAB VALLEY WORLD HERITAGE SITE: LEGAL ISSUES AND STAKEHOLDER COORDINATION - Riad Ferhati; Mohamed Boukader; Maha Messaoudene; Said Madani (International Journal of Innovative Technologies in Social Science, 2024)
The preservation of historic urban centers, although extensively studied, remains a major contemporary issue in the face of societal and environmental changes. The foundational works of Ruskin, Sitte, Giovannoni, Ravéreau, Choay, … as well as the involvement of international organizations such as UNESCO and ICOMOS, have established a theoretical and practical framework for the protection of these sites. In Algeria, the management of historic centers raises crucial governance issues, particularly in a context of rapid and sometimes disorderly urbanization. This issue is particularly relevant for the M’Zab Valley, a UNESCO World Heritage site. This study analyzes the mechanisms of heritage governance in the protected sector of the M’Zab Valley. It specifically examines the articulation between legal and technical instruments for urban development (PDAU) and heritage preservation (PPSMVSS), as well as the interactions between the various stakeholders involved in site management. The methodology is based on two complementary approaches: an analysis of regulatory frameworks and interviews with stakeholders. The results highlight significant dysfunctions, including gaps in steering mechanisms, a lack of coordination between actors, and deficits in skills and solidarity among interveners. The study proposes recommendations aimed at improving the regulatory framework and developing a new governance model promoting better coordination among actors. These proposals aim to optimize the management and preservation of this unique heritage, while taking into account contemporary urban development challenges.